Adhesive bond strength in manually applied concrete repairs: Practical insights and guidelines - De Wit Annelies; Van ranst Michiel; Soetens Tim; Van Belleghem Bjorn (MATEC Web of Conferences, 2025)
This research investigates key factors affecting the adhesive bond strength in manually applied structural concrete repairs, to provide practical guidelines for both the execution of concrete repair and its quality control. A total of 36 patch repairs were conducted on exterior wall panels, with the variation of diverse parameters, such as surface preparation techniques, the use of a bond coat, and curing methods. Adhesive bond strengths were measured at 7, 14, and 28 days through pull-off tests. The results reveal bond strengths did not significantly increase after 7 days, suggesting that on-site quality control with pull-off testing can be conducted earlier than the standard 28 days. Lower substrate (tensile) strength has been found to correlate with a reduced bond strength, presumably as a result of induced damage to the substrate during preparation (concrete removal). Positive effects were observed with bond coat usage and plastic foil curing, while water saturation of the substrate led to a notable decrease in bond strength. The concrete removal and surface preparation technique, the use of an alternative mortar or variations in the water content of the mortar, did not appear to have a significant influence on the bond strength.